Cardiac microcalcification burden is associated with cardiac fat variables in high cardiovascular risk patients. (20th July 2021) - Borges-Rosa, J; Oliveira-Santos, M; Silva, R; Pereira Da Silva, N; Abrunhosa, A; Castelo-Branco, M; Goncalves, L; Ferreira, MJ
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Calcification plays a major role in coronary atherogenesis. Positron emission tomography (PET) imaging with fluorine-18 sodium fluoride (Na[18F]F) is able to detect microcalcification and is associated with cardiovascular (CV) risk factors. Thoracic fat volume (TFV) and epicardial adipose tissue (EAT) are associated with atherosclerosis, pro-inflammatory state, and CV events. Purpose: We aimed to evaluate the association between Na[18F]F uptake and cardiac fat variables. Methods: Cardiac Na[18F]F uptake was assessed as global molecular calcification score (GMCS): the sum of the product of the mean standardized uptake value times the area of the cardiac regions of interest times the slice thickness for all cardiac transaxial slices, divided by the total number of slices. TFV was assessed in computed tomography (CT) using automated software to sum the voxels consisting of fat (threshold of -190 to -30 Hounsfield units) between the bifurcation of pulmonary artery and the end of pericardial sac. EAT was segmented manually tracing the counter of the pericardium with 3DSlicer and the final volume calculated using the dedicated software. Coronary artery calcium score (CAC) was measured with dedicated software for calcium scoring (GE Healthcare Advantage Workstation 4.2). Results: Thirty-four high CV risk individuals without previous CV events (50% with ≥5 CV risk factors) were retrospectively scanned with Na[18F]F PET-CT. Mean age is 63.5 ± 7.8 years and 62% male. Median values are: GMCS 320.9 (240.8-402.8), TFV 167.8 (131.4-211.3) mL, EAT 81.3 (60.7-107.2) cm3, and CAC 0.0 (2.5-20.0). There is a positive correlation between GMCS and abdominal perimeter (rs = 0.74), weight (rs = 0.61), TFV (rs = 0.47), and EAT (rs = 0.41), all with p ≤ 0.01. Thoracic and epicardial fat volumes are strongly correlated (rs = 0.80, p < 0.01). Both TFV and EAT are correlated with abdominal perimeter (rs = 0.60, p < 0.01 and rs = 0.46, p < 0.01, respectively) and weight (rs = 0.47, p < 0.01 and rs = 0.42, p = 0.01, respectively). GMCS [356.7 (321.0-409.6) vs. 261.1 (225.6-342.1), p = 0.01] and thoracic fat volume [184.3 (153.2-303.7) vs. 142.1 (90.0-173.1) mL, p = 0.01] are higher in patients with ≥5 CV risk factors, but not EAT [92.5 (62.0-145.7) vs. 76.7 (56.2-86.8) cm3, p = 0.14]. Neither GMCS (rs=-0.06, p = 0.77), TFV (rs = 0.20, p < 0.32) nor EAT (rs = 0.06, p < 0.76) are correlated with CAC score. Conclusions: In this exploratory analysis with high CV risk patients, the global cardiac microcalcification burden assessed by GMCS is associated with TFV and EAT, but there was no correlation between these variables and CAC. We hypothesize that both GMCS and cardiac fat variables might help to identify higher-risk patients in earlier phases than traditional CT.